Privacy and security issues in mobile health: Current research and future directions. Issue 2 (June 2017) - S. Bhuyan, Soumitra; Kim, Hyunmin; Isehunwa, Oluwaseyi O.; Kumar, Naveen; Bhatt, Jay; Wyant, David K.; Kedia, Satish; Chang, Cyril F.; Dasgupta, Dipankar
Abstract: Mobile health (mHealth) is being recognized as an innovative approach to deliver health care in an accessible, portable and cost effective manner. Despite the numerous benefits associated with the use of mobile devices, there are major concerns with mhealth in the area of privacy and security. These aspects need to be considered at every stage of design and development of mHealth devices and applications which need to be developed by security-trained, trusted manufacturers who should be accountable to minimize damages in the healthcare industry. It is also crucial for users and/or organizations to be more cautious and responsible to use mobile devices. Major stakeholders, including those in the user׳s community (patients and providers), vendors and developers, and policy makers need to come together to survey the landscape, identify the issues, and develop policies, regulations, safeguards and industry standards. Highlights: Major concerns with mHealth in the area of privacy and security. Major stakeholders to come together to survey the landscape and identify the issues. Stakeholders develop policies, safeguards and industry standards to improve mHealth.